Moluscicida a partir do óleo essencial de Hyptis pectinata e de monoterpenos identificados em espécies aromáticas nativas da Amazônia - RIBEIRO, Edilene Carvalho Gomes (2021)
The search for biologically active agents from plant species has enabled the discovery of extremely important substances in the control of various diseases. In view of the diversity of bioactive substances present in essential oils, as well as the epidemiological scenario of schistosomiasis, a neglected disease with a high social and economic impact in the world, this work aims to evaluate the molluscicidal activity of the essential oil (EO ) of Hyptis pectinata (sambacaitá ) and the monoterpenes camphor, 1,8-cineole, α pinene and thymol, against Biomphalaria glabrata snails. The EO was extracted from the leaves of H. pectinata by hydrodistillation. The chemical composition analysis of essential oil was carried out by gas chromatography with flame ionization detector and mass spectrometry. The camphor, 1,8-cineole, α-pinene and thymol monoterpenes were evaluated individually for the molluscicidal potential. Molluscicide tests, both for EO and monoterpenes, were performed according to the standard methodology of the World Health Organization. Toxicity to non-target organisms was evaluated in fish of the species Danio rerio, according to the methodology of the Brazilian Association of Technical Standards. The H. pectinata showed a 1.5% yield and 21 compounds were identified. The molluscicidal activity exhibited by the EO against B. glabrata was significant with LC90 63.02 μg ∙ mL-1. Regarding monoterpenes, camphor and 1,8- cineole did not induce snail mortality. Thymol and α-pinene were active against B. glabrata, causing mortality in concentration-dependent and LC90 7.11 μg ∙ mL-1 and 10.34 μg ∙ mL-1, respectively. The effect of thymol and α-pinene on inhibition of acetylcholinesterase (AChE) activity of B. glabrata was examined. This activity was determined according to the Ellman method. The results showed that thymol and α pinene are inhibitors of AChE of B. glabrata, but at higher concentrations than those used in the molluscicide test. The H. pectinata oil and the monoterpenes thymol and α pinene, showed low toxicity for D. rerio fish compared to the commercial molluscicide niclosamide. The knowledge of the toxicity of H. pectinata oil and of the monoterpenes thymol and α-pinene against B. glabrata contributes to its potential use in molluscicidal and alternative formulations in the control of schistosomiasis.